Influência da radiação gama na oviposição e longevidade de Callosobruchus maculatus (Fabr., 1972) (Coleoptera, Bruchidae) - Walder, Julio Marcos Melges; Wiendl, Frederico Maximiliano (Anais da Sociedade Entomológica do Brasil, 1973)
Gamma radiotion influence on oviposition and Iongevity of Calosobruchus maculatus (Fabr., 1972) (Col. Bruchidae). It was verified Calosobruchus maculatus (Fabr.), a serious pest attacking seeds of ,'ua sinensis, is highly susceptible ro gamma radiacion íor sterilizacion. A dosis of 5 krad causes che egg Lercility to decrease from 90% to only 1%. Adults irradiated with 10 krad become totaily infertile. Doses of 10 krad and more cause an increase of abouc 19% in che longevity of females, but decreases the longevicy of males by abour 5%. Also, irradiacion causes a decrease in che total number of eggs, inversely proporcional to the dosage increase.